Abdominal wall muscles and hernias (Henry Stewart Talks, 2025)
Structure of abdominal wall muscles, Roles of abdominal wall muscles, Nerve supply of abdominal muscles, Formation and risk factors of hernias, Types of abdominal hernias, Diagnosis of hernias, Treatment and prevention of hernias